plis rozwiąż przykłady e,f,g,h,i​



Plis Rozwiąż Przykłady Efghi class=

Odpowiedź :

e) 2/9 * 4,5 - 1/7 = 2/9 * 45/10 - 1/7 = 1 - 1/7 = 6/7

f) 12  3/7 + 3/10 * 5/6 = 12  3/7 + 1/4 = 12  12/28 + 7/28 = 12  19/28

g) 3/8 - 1/3 * 1/4 = 3/8 - 1/12 = 9/24 - 2/24 = 7/24

h) 56/9 : 14/3 + 1,4 = 56/9 * 3/14 + 1  2/5 = 4/3 + 1  2/5 = 1  1/3 + 1  2/5 =

= 1  5/15 + 1  6/15 = 2  11/15

i) 1,2 - 42/100 * 2/7 = 1,2 - 12/100 = 1,2 - 0,12 = 1,20 - 0,12 = 1,08

:)

Szczegółowe wyjaśnienie:

[tex]e)\\\dfrac{2}{9}\cdot4,5-\dfrac{1}{7}=\dfrac{2\!\!\!\!\diagup^1}{9\!\!\!\!\diagup_1}\cdot\dfrac{45\!\!\!\!\!\diagup^{9\!\!\!\!\!\diagup^1}}{10\!\!\!\!\!\diagup_{2\!\!\!\!\diagup_1}}-\dfrac{1}{7}=1-\dfrac{1}{7}=\dfrac{7}{7}-\dfrac{1}{7}=\dfrac{7-1}{7}=\dfrac{6}{7}[/tex]

[tex]f)\\12\dfrac{3}{7}+0,3\cdot\dfrac{5}{6}=12\dfrac{3}{7}+\dfrac{3\!\!\!\!\diagup^1}{10\!\!\!\!\!\diagup_2}\cdot\dfrac{5\!\!\!\!\diagup^1}{6\!\!\!\!\diagup_2}=12\dfrac{3}{7}+\dfrac{1}{4}=12\dfrac{3\cdot4}{7\cdot4}+\dfrac{1\cdot7}{4\cdot7}\\\\=12\dfrac{12}{28}+\dfrac{7}{28}=12\dfrac{12+7}{28}=12\dfrac{19}{28}[/tex]

[tex]g)\\\dfrac{3}{8}-\dfrac{1}{3}\cdot0,25=\dfrac{3}{8}-\dfrac{1}{3}\cdot\dfrac{25\!\!\!\!\!\!\diagup^1}{100\!\!\!\!\!\diagup_4}=\dfrac{3}{8}-\dfrac{1}{12}=\dfrac{3\cdot3}{8\cdot3}-\dfrac{1\cdot2}{12\cdot2}=\dfrac{9}{24}-\dfrac{2}{24}=\dfrac{9-2}{24}=\dfrac{7}{24}[/tex]

[tex]h)\\6\dfrac{2}{9}:4\dfrac{2}{3}+1,4=\dfrac{9\cdot6+2}{9}:\dfrac{3\cdot4+2}{3}+\dfrac{14\!\!\!\!\!\diagup^7}{10\!\!\!\!\!\diagup_5}=\dfrac{56}{9}:\dfrac{14}{3}+\dfrac{7}{5}\\\\=\dfrac{56\!\!\!\!\!\!\diagup^4}{9\!\!\!\!\diagup_3}\cdot\dfrac{3\!\!\!\!\diagup^1}{14\!\!\!\!\!\!\diagup_1}+\dfrac{7}{5}=\dfrac{4}{3}+\dfrac{7}{5}=\dfrac{4\cdot5}{3\cdot5}+\dfrac{7\cdot3}{5\cdot3}=\dfrac{20}{15}+\dfrac{21}{15}=\dfrac{20+21}{15}=\dfrac{41}{15}=2\dfrac{11}{15}[/tex]

[tex]i)\\1\dfrac{1}{5}-0,42\cdot\dfrac{2}{7}=1\dfrac{1}{5}-\dfrac{42\!\!\!\!\!\diagup^{6\!\!\!\!\diagup^3}}{100\!\!\!\!\!\diagup_{50\!\!\!\!\!\diagup_{25}}}\cdot\dfrac{2\!\!\!\!\diagup^1}{7\!\!\!\!\diagup_1}=1\dfrac{1}{5}-\dfrac{3}{25}=1\dfrac{1\cdot5}{5\cdot5}-\dfrac{3}{25}\\\\=1\dfrac{5}{25}-\dfrac{3}{25}=1\dfrac{5-3}{25}=1\dfrac{2}{25}[/tex]